2011
DOI: 10.1002/jobm.201000367
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic comparison of urease‐positive thermophilic Campylobacter (UPTC) and urease‐negative (UN) C. lari

Abstract: Campylobacter lari is frequently isolated from shore birds and can cause illness in humans. Here, we report the draft whole-genome sequence of a urease-positive strain of C. lari that was isolated in estuarial water on the coast of Delaware, USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…At each step, the two nearest clusters are combined into a higher-level cluster, based on the average distance between elements of each cluster. UPGMA was reported to produce adequate results for genome-based clustering of bacteria on the subspecies level ( 46 ). The main disadvantage of UPGMA is the ‘molecular clock’ assumption, which pre-supposes a constant rate of changes in all lineages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each step, the two nearest clusters are combined into a higher-level cluster, based on the average distance between elements of each cluster. UPGMA was reported to produce adequate results for genome-based clustering of bacteria on the subspecies level ( 46 ). The main disadvantage of UPGMA is the ‘molecular clock’ assumption, which pre-supposes a constant rate of changes in all lineages.…”
Section: Resultsmentioning
confidence: 99%
“…Its improved version, BIONJ, chooses the reduction, which minimizes the variance of a new distance matrix at each step of matrix reduction, allowing better estimations for selection of the pair of taxa to be agglomerated during the next steps ( 42 ). The ability of both UPGMA and NJ methods to differentiate various taxa depends on the underlying structure of the data used to construct the dissimilarity matrix ( 46 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three composite full-length gene sequences of ciaB, flaC, and vacJ were shown to be reliable for discrimination between UN C. lari and UPTC organisms, using the UPGMA method, as well as for the differentiation among the four thermophilic Campylobacter species (Hirayama et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our research group demonstrated that fulllength Campylobacter invasion antigen B (ciaB), dnaK, flagellin C (flaC), and virulence-associated chromosome J (vacJ) gene sequence information were reliable for the discrimination between UN C. lari and UPTC taxa, separating from more than other 10 thermophilic Campylobacter isolates, including C. jejuni, C. coli, and C. upsaliensis, using the UPGMA dendrogram (Hirayama et al 2011). Three composite full-length gene sequences of ciaB, flaC, and vacJ were shown to be reliable for discrimination between UN C. lari and UPTC organisms, using the UPGMA method, as well as for the differentiation among the four thermophilic Campylobacter species (Hirayama et al 2011).…”
Section: Discussionmentioning
confidence: 99%